Measurable bundles of C*-dynamical systems and its applications - Ganiev, Inomjon; Mukhamedov, Farrukh (Birkhuser Basel, 2014)
In the present paper we investigate -valued states and Markov operators on -algebras over . Here, is the algebra of equivalence classes of complex measurable functions on . In particular, we give representations for -valued states and Markov operators on -algebras over , respectively, as measurable bundles of states and Markov operators. Moreover, we apply the obtained representations to study certain ergodic properties of -dynamical systems over .